Mothers’ satisfaction with immediate postnatal care provided at ndola central hospital, zambia - Zulu, Mutinke; Chanda, Dorothy (International Journal of Nursing Research, 2023)
Background: Many mothers and their babies do not receive the recommended immediate Postnatal Care. This results in dissatisfaction among mothers and increased neonatal and maternal mortality. At Ndola Central Hospital, mothers complain of poor care. Between January 2011 and December 2013, a total of 265 and 47 cases of neonatal and maternal mortality were recorded. The objective of this study was to determine the mothers’ satisfaction with the immediate Postnatal Care provided at Ndola Central Hospital. Methods: This was a hospital-based cross-sectional study comprising of 202 purposively selected mothers in the immediate postnatal period. A structured interview schedule was used for data collection. It had six satisfaction subscales namely; information, communication, care and comfort, value and preferences, orientation and care specific to postnatal on a five-point Likert scale. It also had 11 socio-demographic and obstetric characteristics. Mothers were interviewed one at a time. Stata version 10.0 was used for data analysis. Spearman’s correlation coefficient (r) was applied to investigate the association between variables. Linear regression modelling was done to test the significance of the association. Results: Only 26.2% of the mothers were fully satisfied with the immediate Postnatal Care. Most mothers were not satisfied with the information they received. The mothers’ employment status and the baby’s condition at birth had statistically significant association with satisfaction. Conclusion: Mothers were not fully satisfied with the Care. Periodic evaluation of the Postnatal Care must be done in order to improve the quality of care delivered, reduce neonatal and maternal mortality and satisfy the mothers.